(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article technology to improve the professional preparation of teachers, the secondary system “technology” role and place of science, technology and teacher preparation in terms of its further development paradigmalar new major theoretical trends cited. Also, the historical aspects of the preparation of future technology teachers professional majorarei and students in technological literacy, critical, creative and systematic thinking, independent decision to take the show will get their intellectual abilities and perfect as a spiritual entity formation to‘g‘provides information on rising.